Pemberdayaan Perempuan Pesisir Dalam Pengelolaan Ikan Di Desa Gerongan Kecamatan Kraton Kabupaten Pasuruan - Aslikhah (Institute for Research and Community Service in Universitas Yudharta Pasuruan, 2019)
The potential of fishpond aquaculture in Pasuruan Regency will have more value if it is balanced with the ability of Human Resources to process the fishery products into products that have added value, especially for women, most of whom still do not have economic independence. The purpose of this community service is to find out how to empower coastal women in processing of fish farming in coastal areas in Gerongan Village, Kraton Subdistrict, Pasuruan Regency.The method used in assisting coastal women in fish processing to increase added value in Gerongan village, Kraton sub-district of Pasuruan Regency is to use the Participatory Action Research (PAR) method approach. The Participatory Action Research (PAR) approach was carried out to obtain the initial data needed in this community service program by actively involving all parties, namely lecturers and students of the University of Yudharta Pasuruan as well as the community in Gerongan Village, Kraton Subdistrict, Pasuruan Regency. From this empowerment, coastal women are expected to be able to improve their skills in processing fish products from fishpond ponds so that they can increase their productive farming efforts and have a role in helping to increase income to meet family needs.